TRUE OWNERS OF THE LAND: THE PROTECTION OF PEOPLE ORIGINATING IN BRAZIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The Indians are the original people and true owners of the land. These were accused of, for a long period, actions mitigating their fundamental rights and guarantees, perpetrating a past of injustice and violence. Therefore, the present work set out, as its main objective, to investigate the fundamental rights and guarantees granted to original peoples in Brazil. As an accessory, the origin of the Brazilian territory was presented; there was talk about the Federal Constitutions of Brazil and their regulation regarding fundamental rights and guarantees in relation to indigenous peoples. The 1988 Federal Constitution was presented and the guarantee of specific rights to original peoples, such as health, education, property and culture. It was shown that Law 6,001/73, (Indian Statute), was partially accepted by the 1988 Constitution, due to its integralist policy. Finally, the concept of Buen Vivier (Sumak Kawsay) was presented in the Constitutions of Ecuador and Bolivia as a fundamental principle of social development as well as respect for ancestry in relation to original peoples. It was highlighted that in Brazil, the emancipatory multicultural policy is in force, and it should adopt an intercultural policy in the medium-long term. The work is justified by the relevance it assumes in the social, political, academic and economic context. The research methodology was deductive, data collection carried out qualitatively through bibliographical research.